Upaya Peningkatan Penguasaan Kosakata Bahasa Jerman Peserta Didik Kelas XI MIPA 5 SMA Negeri 1 Sedayu melalui Aplikasi Duolingo - Wahyuningtias, Seftyana Utami; Santoso, Iman (Nexus Publishing, 2024)
The objectives of this study are: (1) to increase learners' vocabulary mastery in German class and (2)) to increase learners' participation in class from Class XI MIPA 5 of SMA Negeri 1 Sedayu through Duolingo Aplication. In this study, a classroom action research (CAR). The subjects of the study are 34 learners from class XI MIPA 5 at SMA Negeri 1 Sedayu. The data will be collected qualitatively and analyzed descriptively. This research is divided into two cycles. Each action consists of four stages: planning, implementation of the action, and observation and reflection phase. The indicators of success are (1) the success of the product (the grade point average) and (2) the success of the process (the participation of the learners). The result of this research shows that the Duolingo application (1) can increase learners' vocabulary. The average vocabulary score increased by 38%, and (2) learner participation in the class increased by 40%.